Strengthening The Capacity of Indonesian Migrant Workers Through Old-Age Social Security A Study on PMI in Malaysia and Hongkong - Agusmidah Agusmidah; Yefrizawati Yefrizawati; Affila Affila; Zulfi Chairi; Farhan Alpani Pane; Rajali H. Aji (Fiat Justisia: Jurnal Ilmu Hukum, 2026)
Indonesian Migrant Workers (PMI) are primarily motivated to work abroad by the prospect of higher wages to achieve long-term financial security, despite the social costs of family separation. However, empirical evidence from observations, interviews, and questionnaires reveals that many PMIs have limited understanding of the old-age pension scheme, a key component of the national social security system, a gap exacerbated by inadequate pre-departure briefings for prospective migrant workers (CPMI) despite clear legal obligations. This study employs an empirical juridical method supported by a conceptual legal approach to examine the gap between the normative framework governing PMI social security protection and its implementation in practice, particularly regarding technical barriers to paying old-age security contributions during overseas employment. The findings show weak institutional coordination and accountability among key stakeholders, including the Ministry of Manpower, BPJS Ketenagakerjaan, BP2MI, the Ministry of Foreign Affairs, and state-affiliated banking institutions. The study concludes that strengthening legal compliance, inter-agency coordination, and accessible contribution mechanisms is essential to ensure effective protection and the realization of old-age social security rights for PMIs after the completion of their employment.